ClinicaI Reversible Myelopathy in T-Cell Lymphoblastic Lymphoma Treated with Nelarabine and Radiotherapy: Report of a Case and Review of Literature of an Increasing Complication - Maria Chiara Tisi; Giuseppe Ausoni; Maria Gabriella Vita; Tommaso Tartaglione; Mario Balducci; Luca Laurenti; Patrizia Chiusolo; Stefan Hohaus; Simona Sica (Mediterranean Journal of Hematology and Infectious Diseases)
To date, eleven cases of irreversible neurological defects in T- ALL patients treated with nelarabine have been described in the last 4 years, seven of these after stem cell transplantation (SCT) for T Lymphoblastic Lymphoma (T-LBL). Most of patients had an unfavorable outcome or irreversible damage.